(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The need for an enhanced word processing and database management competencies acquisition by Office Technology and Management Education (OTME) students for success in employment, necessitated this study. Two research questions guided the study and two null hypotheses were tested. Descriptive survey research design was adopted for the study. The population consisted of 98, 2016/2017 session final year OTME students in all colleges of education in Delta State. The entire population was studied without sampling as the size was small. A five-point rating scale questionnaire containing 26 items was used for collecting data for the study. The instrument was validated by three experts in the faculty of education, Nnamdi Azikiwe University, Awka. The reliability of the instrument was established by administering it to 10 respondents from College of Education, Ekiadolor in Edo State. Using Cronbach Alpha method, a reliability coefficient of 0.87 was obtained. Mean and standard deviation were used to answer research questions and determine the closeness of respondents’ views. While t-test was used to test the null hypotheses at 0.05level of significance. Findings revealed that the students rated themselves to have acquired word processing and database management competencies at moderate level and gender did not significantly influence their ratings. Based on the findings, it was concluded that more efforts were needed by the students, their lecturers and the institution managements to ensure that students adequately acquire relevant competencies in the two applications for them to be effective in carrying out their professional responsibilities on graduation. It was, therefore, recommended among others that OTME students should use computers instead of typewriters right from their first year and that institutions managements should provide adequate number of functional computers for use by the students.